Pharmacogenetic inhibition of the infralimbic cortex promotes reinstatement of cocaine-context memories in mice. - Pérez-Cano, Ana María; Ávila-Gámiz, Fabiola; Pérez Berlanga, José Manuel; Santín-Núñez, Luis Javier; Ladrón de Guevara-Miranda, David (My University, 2023)
Relapse is one of the main problems concerning treatment of cocaine use disorder. It have been suggested that the infralimbic cortex (IL), a division of the medial prefrontal cortex, is involved in extinction and reinstatement of associative memories, including those involving drugs. However, more selective strategies are needed to elucidate the involvement of IL in the long-term maintenance of drug-related maladaptive behaviours. Here, we employed pharmacogenetics to assess the causal role of IL in the reinstatement of a cocaine-induced conditioned place preference (CPP). For this purpose, adult C57BL/6J mice received bilateral intra-IL microinjections of an adeno-associated viral (AAV) vector containing the hM4Di designed receptor (AAV5-CaMKII-hM4Di-mCherry; AAV-hM4Di, n=11) or a control vector (AAV5-CaMKII-mCherry; AAV-control, n=9) prior receiving training in the cocaine-induced CPP model. After habituation, animals received compartment-paired conditioning by increasing doses of cocaine (2-16 mg/kg/day, i.p.) and were tested for cocaine-CPP, after which they were subjected to forced CPP extinction and then re-tested for cocaine-CPP. On day 37 after AAV infusion, mice received Clozapine N-oxide (CNO, 5 mg/kg, i.p.) and 30 min later were tested for cocaine-primed (7.5 mg/kg, i.p.) CPP reinstatement. Ninety minutes after, animals were perfused, and brains dissected. Our results indicated that both groups acquired and subsequently extinguished cocaine-CPP. However, only the AAV-hM4Di group showed a significant preference for the cocaine-paired compartment during the CPP reinstatement test. Immunofluorescence analyses of c-Fos expression in IL revealed a decrease of ~60% in mCherry+/c-Fos+ co-labelling in the AAV-hM4Di group, suggesting reduced IL neural activity during CPP reinstatement. Therefore, our data suggests that the IL plays a causal role in relapse to cocaine-related maladaptive behaviours, highlighting its importance as a potential therapeutic target.
Funding: PID2020-113806RB-I00, 08-2021-AREA3, B1-2020_06, FPU20/00908, PRE2018-085673, PREDOC_01094, POSTDOC_ 21_00222. II Plan Propio de Investigación, Transferencia y Divulgación Científica de la UMA.
Keywords: Drogas - Efectos fisiológicos; Cocaína - Efectos fisiológicos; Cocaine; DREADD; Inhibition; Prefrontal cortex; Relapse